Emergence and Associated Risk Factors of Vector Borne West Nile Virus Infection in Ilorin, Nigeria - Olatunji Matthew Kolawole; Glory Adelaiye; Jeremiah Ikhevha Ogah (Tehran University of Medical Sciences, 2018)
Background: West Nile Virus (WNV) is a mosquito-borne viral pathogen that is the causative agent of West Nile fever and encephalitis. Diagnostic tools for WNV infection in Nigeria are not well established hence the current prevalence rate of WNV infection in Nigeria is unknown. We aimed to establish the serological prevalence of WNV infection in febrile patients in Ilorin, Nigeria in 2016, and to assess the risk factors associated with the acquisition of the virus. Methods: This was a cross-sectional study involving the screening of subjects presenting with febrile illnesses. While specific IgM ELISA was used to determine the seroprevalence, a closed-ended questionnaire was used to ascertain the risk factors associated with this viral infection. Results: Fifteen (7.5%) of the respondents were positive for WNV infection. Subjects living in areas in close proximity to trees and bushes (P= 0.011) and stagnant water (P= 0.001) were at a higher risk of having WNV infection. Other risk factors associated with WNV among the respondents include the none use of insecticide (P= 0.001), sitting out at night (P= 0.044), HIV positivity (P= 0.003) and having an organ transplant (P= 0.002). Conclusion: This study clearly shows a considerable WNV infection in Ilorin, with the presence of factors that can promulgate an outbreak, hence a need for further surveillance in the study area.